2013
DOI: 10.1089/aid.2012.0330
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunovirologic Outcomes with Maraviroc Combination Regimens in Patients with a History of Past Treatment Failures and Virologic Resistance in Brazil: An Open-Label, Multicenter Phase 3b Study

Abstract: Maraviroc is a first-in-class chemokine coreceptor type-5 (CCR5) antagonist with demonstrated immunovirologic activity in treatment-experienced (TE) patients with CCR5 (R5)-tropic HIV-1; however, experience in regimens containing newer antiretroviral agents is limited. The primary objective of this 96-week open-label, noncomparative, multicenter Phase 3b study (NCT00478231) was to assess the safety of maraviroc in combination with optimized background therapy (OBT), which could include recently introduced agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Additional safety and immunovirologic ativity data of Maraviroc in regimens were obtained after newer agents such as darunavir, raltegravir, and etravirine were clinically available [41]. It was found that Maraviroc was well tolerated over 96 weeks as a combination with different agents, and treatment with Maraviroc in combination with OBT was associated with significantly greater immunovirologic activity versus placebo plus OBT [40, 41]. …”
Section: Clinical Studiesmentioning
confidence: 99%
“…Additional safety and immunovirologic ativity data of Maraviroc in regimens were obtained after newer agents such as darunavir, raltegravir, and etravirine were clinically available [41]. It was found that Maraviroc was well tolerated over 96 weeks as a combination with different agents, and treatment with Maraviroc in combination with OBT was associated with significantly greater immunovirologic activity versus placebo plus OBT [40, 41]. …”
Section: Clinical Studiesmentioning
confidence: 99%
“…2933 In Brazil, in the adult population failing first- and second-line therapy, maraviroc susceptibility ranges from 42% to 70%s in different cities. 34,35 A pediatric study in São Paulo city found 45% in use of maraviroc. 36 A lack of virological suppression associated with improper cART adherence is related to viral resistance.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 The association of subtype C and R5 tropism, considering all patients have been infected for an extensive period of time, is also previously reported that indicates the occurrence of X4 or dual tropic virus appears to be rare in this clade. 1743 A conserved nature of HIV-1 C subtype V3 sequence may reduce the possibility of coreceptor switch in these viruses, which may explain the low prevalence of X4-tropic in this population. 44 Nevertheless, a study conducted in India, which included only HIV-1 subtype C perinatally-infected patients, showed a higher prevalence of X4 tropic strains in an older population.…”
Section: Discussionmentioning
confidence: 99%
“…26 BRIGHTE required that participants had eliminated all ARV options from ≥4 classes for resistance, previous side effects, contraindications, or unwillingness to use enfuvirtide (a twice-daily injectable). 27,28 All five studies in Periods 2 and 3 required that participants had ≥1 fully active ARV that could be used in the background regimen, but only BRIGHTE limited inclusion to those who had active 35,40,43,45,47,50,51,53,56,62,63,66,76,81,83,93,94,103,104 --Phase 3 or 3b 24/89 (27) 12,14,[16][17][18][19][20][21][22]28,32,34,39,41,46,52,55,57,65,75,105 3 23-25 2 26,27 Randomized (fully or partially) 59/89 (66) 13,14,[16][17][18...…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Blinded (fully or partially) 21/89 (24) 12,14,17,19,20,[39][40][41]43,45,[51][52][53]62,66,67,103,106 1 24 1 27 Non-inferiority 9/89 (10) 19,34,41,42,46,50,57,105,111 14,[20][21][22][30][31][32]35,37,[40][41][42][43][45][46][47][48]50,53,[56][57][58]61,65,75,…”
Section: Inclusion Criteriamentioning
confidence: 99%